A status and prospects of organizing the cultural events as exemplified by the "Ustuu-Khuree” International festival of live music and faith - Dulush, Igor D. (The New Research of Tuva, 2012)
A report by the Director of the "Ustuu-Khuree” Festival, Director of the Tuvan State Philharmonic Hall at the round table "Ethnotourism as a factor of territory development” within the framework of 2nd International Touristic Forum "Tuva: An Intersection of Roads and Cultures” (Kyzyl, April 6, 2012).